Game Localisation: Loss and Gain in Visual Novel Subtitles - Etty Syafa’ati; Umi Pujiyanti (Register Journal, 2017)
This research discussed about loss and gain in the context of game localization with the limitation on subtitles. The objectives are to present the loss and gain in the visual novel game adaptation subtitles entitled A Child in the Forest and to identify reasons of the loss and gain happen. A Child in the Forest is a kind of game which consists of static and background images also music soundtrack with storylines and dialogues. It was made and translated from English into Indonesian version by English Letters students of IAIN Surakarta. The method used in this research is descriptive qualitative. The method of collecting data, researcher gets English and Indonesian subtitles script from the game packages. After that, the researcher analyses the data which consist of loss and gain and also make interview with translator. The researcher uses informant to make data validation which is expert in translation and in the world of visual novel game. The result of this research, researcher found 63 data about loss and 55 data about gain. The reasons of loss and gain in visual novel game subtitle is mostly because of the translator wants to reach the goal of game localization in order the visual novel can be easy to be played and to be understood.Keywords: Game Localization, Loss and Gain, Subtitle of Visual Novel Game. INDONESIAN ABSTRACT Penelitian ini membahas tentang loss dan gain dalam konteks game lokalisasi dengan fokus hanya pada subtitle. Tujuan dari penelitian ini adalah untuk menunjukan loss dan gain yang ditemukan serta mengidentifikasi alasan kenapa loss dan gain bisa terjadi di subtitle visual novel game adaptasi berjudul A Child in the Forest. A Child in the Forest adalah sebuah permainan yang terdiri dari gambar statis dan latar belakang juga suara music dengan alur cerita dan dialog. Visual novel ini dibuat dan diterjemahkan dari bahasa Inggris ke bahasa Indonesia oleh siswa jurusan sastra inggris semester 2 IAIN Surakarta. Metode yang digunakan dalam penelitian ini adalah penelitian deskriptif kualitatif. Metode pengumpulan data, peneliti mendapatkan naskah terjemahan bahasa Inggris dan bahasa Indonesia dari data paket permainan. Setelah itu, peneliti menganalisis data yang mengandung loss dan gain dan juga melakukan wawancara dengan penerjemah. Peneliti menggunakan informan untuk melakukan validasi data yang ahli dalam dunia penerjemahan dan ahli dalam game visual novel. Hasil penelitian ini, peneliti menemukan 63 data tentang loss dan 55 data tentang gain. Alasan loss dan gain dalam subtitle game visual novel ini sebagian besar karena penerjemah ingin mencapai tujuan lokalisasi permainan agar visual novelnya mudah dimainkan dan dipahami.Kata kunci: Lokalisasi Game, Loss dan Gain, Subtitle di Visual Novel Game.